Pengaruh ROE dan DER terhadap Harga Saham pada Perusahaan Sektor Pertambangan Minyak & Gas yang Terdaftar di BEI Periode 2016-2020 - Wizar Sudira; Hari Sulistiyo (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Indonesia is a country with a large population, which will result in a fairly large level of energy demand and one of them is the need for oil and gas. In conditions of global instability and limited supplies of oil and gas resources, this will also have an impact on the condition of companies in this sector in Indonesia. This study aims to examine, identify, and analyze the effect of the ROE and DER ratios on stock prices in oil and gas mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The research method used is descriptive verification, and the number of samples taken from the population is 6 out of 13 companies. The sampling technique used is purposive sampling and uses multiple linear regression analysis tools and uses SPSS analysis tools with the results of DER not having an effect on stock prices and ROE having an effect on stock prices and DER and ROE simultaneously having an effect on stock prices. Keywords: Return on Equity; Debt to Equity Ratio; Stock Price